Hybridization effect on the mechanical properties of basalt fiber reinforced ZnO modified epoxy composites. Issue 8 (12th July 2022) - Joshi, Siddharth; Hiremath, Anupama; Nayak, Suhas Yeshwant; Jaideep, Jeppu Pramod; Thipperudrappa, Sridhar
Abstract: This paper discusses the fabrication of nano ZnO filled epoxy/basalt fiber composites and investigates the effect of such hybridization on the mechanical properties of the composites. The epoxy resin is modified by the addition of ZnO nanofiller in different wt.% (1–5 wt%). The dispersion of the nanofiller within the epoxy resin is brought about by sonication technique. The composites are fabricated through wet layup followed by curing under compression molding. To ascertain the effect of resin modification, flexural and tensile strengths are evaluated. The inter‐laminar shear strength (ILSS) is determined to identify the compatibility of the ZnO nanofiller with the epoxy and the basalt fibers. The improvement in the ILSS indicates thorough wettability being achieved between all the composite components. The addition of ZnO nanofiller improved the flexural strength, while there was no remarkable improvement in the tensile strength of the ZnO modified epoxy/baslat (BEZ) composite. Maximum improvement in the strengths is observed for BEZ2 composite with 2 wt% of ZnO nanofiller. For BEZ2 composite, the flexural and tensile strength increased by about 22% and 9.78% respectively in comparison to unfilled BEZ0 composite. The ILSS for BEZ2 composite improved by 21.74% in comparison to BEZ0 composite. In addition, more than 2 wt% addition of the ZnO nanofiller resulted in the reduction of flexural, tensile and ILSS of the composite due to agglomeration. Such agglomeration resulted in the failure of the composite due to delamination, matrix cracking and fiber fracture as observed through scanning electron microscopy images of the fractured composites. Abstract :